New multiplex conventional PCR and quadruplex real-time PCR assays for one-tube detection of Phyllosticta citricarpa, Elsinoë fawcettii, Elsinoë australis, and Pseudocercospora angolensis in Citrus: development and validation - Ahmed, Yosra; Hussein, Ahmed; Hubert, Jacqueline; Fourrier-Jeandel, Céline; Aguayo, Jaime; Ioos, Renaud (Applied microbiology and biotechnology, 2020)
Phyllosticta citricarpa , Elsinoë fawcettii , Elsinoë australis , and Pseudocercospora angolensis are major pathogens of citrus crops worldwide and can cause non-characteristic symptoms that may lead to confusion regarding the causative agent . These fungi are subject to international phytosanitary regulations, and testing on fruits or leaves requires accurate and easy-to-use tools. New multiplex conventional PCR and real-time PCR assays were developed here to achieve highly accurate simultaneous detection of all four fungal pathogens in fruit tissues. We designed new oligonucleotide combinations for P. citricarpa , E. fawcettii , and E. australis and combined them with already available primers and hydrolysis probes to be used in either PCR assay. The limit of detection for multiplex conventional PCR was as low as 100 pg μL −1 for P. citricarpa , E. fawcettii , and E. australis and 10 pg μL −1 of target DNA per reaction tube for P. angolensis. The quadruplex real-time PCR assay successfully yielded repeatable positive results with as low as 242, 243, 241, and 242 plasmidic copies of target DNA of P. citricarpa , E. fawcettii , E. australis , and P. angolensis , respectively. Moreover, analysis of 60 naturally infected citrus samples yielded 100% concordant results by both assays. Our validation experiment revealed that the multiplex real-time PCR assay showed high specificity except a cross-reaction with P. paracitricarpa DNA. Sensitivity, repeatability, reproducibility, and robustness were verified, and the assay could be used following different DNA extraction procedures, supporting fitness for routine analysis. These new multiplex tools should be of great interest as cost-effective solutions for regulatory authorities and diagnostic laboratories, enabling testing for four important pathogens in single-tube reactions. Key points • Development of new conventional PCR and qPCR assays for four citrus pathogens. • Very low limits of detection were found for multiplex conventional PCR. • qPCR had high specificity, sensitivity, repeatability, reproducibility, and robustness.